2009
DOI: 10.1001/archsurg.2009.154
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized Plasma for Resuscitation in a Swine Model of Severe Injury

Abstract: The process of lyophilization and reconstitution of plasma reduces coagulation factor activity by 14%, without acute differences in blood loss. Lyophilized plasma can be used for resuscitation in a severe multiple trauma and hemorrhagic shock swine model with efficacy equal to that of FFP and with decreased interleukin 6 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…14,15 As previously discussed, the 1:1 LP to PRBC group demonstrated the lowest blood loss after grade V liver injury. 7 The combination of the RBC effects on clot formation with the superior coagulation factor activity of LP may have synergistic effects on hemostasis and may explain the decreased blood loss compared with 1:1 FFP to PRBC, LP alone, and FFP alone. The absence of significant differences in PT, fibrinogen, and ionized calcium levels between fluid groups at postinjury time points emphasizes the inadequacy of these tests in assessing coagulation status in hemorrhagic shock and polytrauma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 As previously discussed, the 1:1 LP to PRBC group demonstrated the lowest blood loss after grade V liver injury. 7 The combination of the RBC effects on clot formation with the superior coagulation factor activity of LP may have synergistic effects on hemostasis and may explain the decreased blood loss compared with 1:1 FFP to PRBC, LP alone, and FFP alone. The absence of significant differences in PT, fibrinogen, and ionized calcium levels between fluid groups at postinjury time points emphasizes the inadequacy of these tests in assessing coagulation status in hemorrhagic shock and polytrauma.…”
Section: Discussionmentioning
confidence: 99%
“…6 We have previously shown that LP maintains 86% coagulation factor activity, and the use of LP in a 1:1 ratio with packed RBC (PRBC) results in significantly less blood loss after liver injury when compared with 1:1 ratios of FFP to PRBC, FFP alone, and LP alone. 7 The observed decrease in blood loss was not adequately explained by the results of standard coagulation tests that revealed an increased activated partial thromboplastin time (PTT) in the 1:1 LP to PRBC group and no difference in prothrombin time (PT) between groups. The contribution of RBCs in correcting coagulopathy is poorly understood.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, our MT protocol includes the preferential use of RBCs with less than 14 days of storage [9,10] because of the high risk of adverse events that have been associated with the transfusion of older RBCs to critically ill patients [1,6,[11][12][13]. Red blood cells with more than 14 days of storage have been independently associated with increased multiorgan failure in 2 separate large prospective studies in critically ill children [9,10] and increased mortality in adults with severe traumatic injury [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was, however, to evaluate the effects of FFP resuscitation, and we thus opted to use this fluid without additional PRBCs and PLTs because this would, in essence, have evaluated the synergistic effects of these combined resuscitation strategies, rather than the effect of FFP alone. Further, studies have indicated that freeze-dried FFP may be equally efficacious, 26,27 which may indicate a potential role for FFP-based products in early prehospital resuscitation. Our choice of NS as a control fluid can certainly be debated, but was based on the need for a well-studied, relatively inert control treatment.…”
Section: Figmentioning
confidence: 99%